Postpartum Depression and it’s Homoeopathic Management (Homoeopathy for All, 2024)
Now a days the most commonly seen  conditions during postnatal care are  postpartum blues or baby blues and  postpartum depression.  Postpartum Blues or Baby Blues  are acute in nature and happen to  as many as 70% of women in the  days right after childbirth. Women  experience sudden mood swings such  as crying for no reason or feeling very  impatient, restless, anxious, lonely or  sad. Baby blues may last for a few  hours or as long as 1 to 2 weeks post  delivery. Usually they don’t need any  medical intervention from a health  care provider. But , joining a support  group of new moms or talking with  other moms often helps.
Keywords: Postpartum; experience